Knowledge and practice regarding dental care of head and neck cancer patients undergoing radiotherapy in UP-PGH radiation-oncology department - Agdeppa, Judy G.
Cancer patients undergoing radiotherapy experience a variety of oral complications ranging from xerostomia, radiation caries, mucositis, taste sensation changes and weakened immune response. The health profession has realized the importance of maintaining the integrity of the oral cavity at a time when the patients' immune system is low, and the risk of infection is high. The ■ patients' knowledge and compliance could spare them the discomfort and pain associated with this treatment. It is in this light that the author aimed to determine the awareness and practice of cancer outpatients in UP-PGH Radiation-Oncology Department. A total of 41 subjects were included in the study conducted from the period September 1998 to January 1999. Results revealed that 83% of the subjects were knowledgeable of the basic oral hygiene procedures accorded to them. However, poor patient compliance was observed specifically among those patients with their natural dentition intact,with compliance recorded only at 17% among those subjects wearing removable or fixed partial denture, and 44% among those not wearing any prosthesis and with their natural dentition in place.